Victim Protection - Juniati, Juniati Juni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The protection of victims that has occurred so far has always been state intervention by using the principles of police power or the relevant legal apparatus. The increasing suffering experienced by victims in a society can cause unrest and the victims of certain weak groups may meet their needs unnaturally and cause further losses and chaos. In this case the consumer isn’t the only White Collar Crime in this consumptive society. With many illegal habits that are carried out by the corporation. In this case, it becomes a study in research in the context of victim protection, because victims are surrounded by powers of power so that it will easily lead to victimization. With the existence of victims as a result of victimization from the work of the bureaucracy, as a result of the bureaucracy that may lead to victimization of a person or group, this has an influence on society at large. The perpetrators of corporate crimes are the target of focused attention in creating the current regulations, considering specific penalties. Targeted products are gradually attracting the attention of product designers and lawmakers who recognize that crime-free product design may predate many crimes. In the context of repeated victimization, the structural constraints are real and serious, and that this research can look at how context shapes and influences victim behavior routines. The research method used is a qualitative approach adapted to the needs of the research, namely obtaining in-depth explanations and information regarding efforts to protect victims of corporate crime. The plan in the research of research informants is the main key to explain problems that can result in victims. The object of this research is the Project X Corporation.